Website-Based Online Sales Information System at the Sarto Sapi Company - Erix Yoga Pratama Putra Bakti; Maria Atik Sunarti Ekowati (Journal of International Multidisciplinary Research, 2023)
The Sarto Sapi Company is one of the providers of cattle sales services which is located in Jebol Hamlet RT 001 RW 007, Donohudan, Regency Boyolali, with sales still done manually. Objective The research is the development of a website-based online sales information system for the Sarto Sapi Company to facilitate access for customers who want to shop online without having to come directly to the Sarto Sapi Company. The website developed is a means of selling cattle as well as a means of conveying information to the public. The method used in developing a website-based online sales information system at the Sarto Sapi Company is the Waterfall method. The Waterfall method is used to determine system requirements, the next step is the analysis, design, coding, testing and maintenance stages. Development of a Website-Based Online Sales Information System at the Sarto Sapi Company, researchers used notepad++ software, sublime text, the PHP programming language, and MySQLi database. Results of research on developing a website-based online sales information system at the Sarto Sapi company, online sales website. National Journal Research Output